Complete chloroplast genome of a Chinese endemic species Corydalis trisecta Franch. (Papaveraceae). Issue 2 (3rd July 2019) - Kanwal, Nazish; Zhang, Xiao; Afzal, Nawal; Yang, Jia; Li, Zhonghu; Zhao, Guifang
Abstract: Corydalis trisecta Franch. is an endemic plant found in China. In this study, we presented the first complete chloroplast genome of C. trisecta, which was assembled and characterized based on Illumina pair-end sequencing data. The complete chloroplast genome was 161, 410 bp in length, with a GC content of 41.4% in total. Its structure contained a large single copy (LSC) region of 89, 127 bp and a small single copy (SSC) region of 16, 993 bp, which were separated by a pair of extremely inverted repeats (IRs) of 27, 645 bp each, with GC content 39.8, 87.2, and 45.2%, respectively. The phylogenetic analysis indicated that C. triscta was sister to Lamprocapons spectabilis in Papaveraceae.